Price Transmission and Trader Entry in Domestic Commodity Markets. - Fafchamps, M; Hill, R (GPRG, 2005)
Using detailed data from three simultaneous surveys of producers, traders, and exporters, this paper examines the transmission of international co¤ee prices through the domestic value chain in Uganda. We …find that producer prices fluctuations are inconsistent with constant transactions costs. We investigate two possible explanations for this …nding: marketing costs that increase with price, and trader entry. We test and reject the marketing costs explanation but we …nd some evidence of trader entry in response to a rise in export price. Our …ndings suggest that small itinerant traders initiate co¤ee trading in response to an export price increase, probably taking advantage of farmers'ignorance of price movements.